Réponses

2014-09-25T10:50:01+02:00
F(x) = (2x+3)(4x+1-5) = 4(2x+3)(x-1) = 4(2x² + x - 3 ) = 8x² + 4x - 4 
f(0) = -4
4(2x² + x - 3 ) = 0  => (2x² + x - 3 ) = 0 
Δ = 1 + 24 = 25 => x1 = (-1 - 5)/4 = -3/2 ou x2 = (-1 + 5)/4 = 1
les antécédents sont -3/2 et 1 

2014-09-25T11:06:04+02:00
Factoriser f(x)=(4x+1)(2x+3)-5(2x+3)
f(x) = (2x+3)[(4x+1) - 5]
f(x) = (2x+3)(4x-4)

Développer f(x)
f(x) = (8x² +12x + 2x + 3) - (10x + 15)
f(x) = 8x² + 12x + 2x + 3 - 10x - 15
f(x) = 8x² + 4x - 12

f(0) = 8(0)² + 4(0) - 12
f(0) = 12

Calculer l'image de 0 par f
f(0) = 8(0)² + 4(0) - 12
f(0) = 12

Déterminer les antécédents de 0 par f
(2x+3)(4x-4) = 0
2x+3 = 0
     2x = -3
x = -3/2


4x-4 = 0
 4x = 4
x = 4/4
x = 1